The impact of the National Syphilis Prevention Program on the prevalence of syphilis among people living with HIV in China: a systematic review and meta‐analysis - Qingling Zeng; Yuhui Yang; Limin Zhang; Jiangyu Yan; Jian Wang; Jingmin Nie; Qingmei Wang; Yu Luo; Gaoming Li (Journal of the International AIDS Society)
Abstract Introduction In 2010, China launched the 10‐year National Syphilis Prevention and Control Program to curb the spread of syphilis by integrating syphilis screening and treatment with HIV services. Herein, we aimed to evaluate changes in the prevalence of syphilis among people living with HIV (PLHIV) in China. Methods We conducted this systematic review and meta‐analysis by searching the PubMed, Embase, Web of Science, China Biomedical Literature, China National Knowledge Infrastructure, Wanfang and CQVIP databases from inception to 1 June 2024 to obtain relevant articles. A total of 75 studies were ultimately included. We used a DerSimonian‒Laird random effects model to estimate the prevalence and 95% confidence interval of syphilis among PLHIV. Results The overall prevalence of syphilis among PLHIV in China was 18.6% (95% CI 16.5–21.0). Regional differences (R2 = 15.29%) were observed in the prevalence rates: 22.2% (18.9–25.8) in the eastern region, 19.0% (15.1–23.8) in the central region and 14.0% (11.1–17.5) in the western region. The prevalence decreased from 22.8% (18.4–27.9) before 2010 to 17.0% (14.6–19.6) in 2010 and thereafter (R2 = 5.82%). Among PLHIV via homosexual transmission, the prevalence of syphilis was 24.9% (21.3–28.9), which significantly declined from 33.8% (27.5–40.8) to 21.4% (18.3–24.9) in 2010 and thereafter (R2 = 22.35%). The prevalence of syphilis was significantly higher in men living with HIV than in women living with HIV (pooled odds ratio 1.67, 95% CI 1.29–2.15), with the highest prevalence in the eastern region (2.55, 95% CI 1.80–3.59). Discussion The prevalence of syphilis among PLHIV, particularly in cases of homosexual transmission, has declined. There was a correlation between the prevalence of syphilis and regional economic conditions, with a greater burden in developed eastern coastal areas. Additionally, the risk of syphilis differed across sexes, with men living with HIV having a higher risk. Conclusions There has been preliminary success in the control of syphilis among PLHIV, but there is still a long way to go to meet the WHO's 2030 syphilis prevention and control goal. Syphilis prevention measures should be integrated into broader health policies and development plans, particularly in high‐burden regions and populations.